RULING OUT VSO AND VOS CONSTRUCTIONS IN BRAZILIAN PORTUGUESE - Lacerda, Renato (Estudos Linguísticos e Literários, 2024)
Brazilian Portuguese does not allow verb-subject-object and verb-object-subject constructions; while postverbal transitive subjects are ruled out, postverbal subjects are only productive with unaccusative verbs. This paper tackles the issue of postverbal subjects and proposes a formal account of the absence of VSO and VOS constructions in Brazilian Portuguese, which is derived from the combination of two independently-motivated properties of the language: (i) the verbal domain is minimally expanded to include an object shift position at the edge of vP and (ii) the lexical verb moves to a low position in the tense-aspect domain. It is argued that the combination of these two properties of Brazilian Portuguese gives us the result that the postverbal area of the language is “too small” to simultaneously host both a subject and an object.